Burden in Colombia of COVID-19 in Adults and the Associated Clinical Characteristics: A Retrospective Database Analysis - Jair Arciniegas; Juan Manuel Reyes; Jhon Bolaños-López; Julia Regazzini Spinardi; Jingyan Yang; Farzaneh Maleki; Farley Johanna Gonzalez; Carlos Jose Bello; Ana Catalina Herrera-Díaz; Omar Escobar; Andrea Rubio; Monica Garcia; et al. (Tropical Medicine and Infectious Disease)
Studies on the burden of COVID-19 cases in Colombia have focused on specific populations and short timeframes. A retrospective observational study was conducted on adult patients aged 18 diagnosed with COVID-19 who received inpatient and/or outpatient medical care at a large health maintenance organization, to evaluate the burden of COVID-19 cases in Colombia (from March 2020 to January 2023) and associations with demographic and clinical characteristics. COVID-19 cases were identified with ICD-10 codes and confirmed by a laboratory test. The statistical analysis focused on descriptors of the frequency of events. A multivariate regression model was used to identify factors associated with severe conditions and death. Of the 953,661 cases detected, most cases (~79%) were mild or moderate (handled as outpatients). There were 20.1% (N = 191,260) severe cases and 0.9% (N = 8841) critical cases. Most COVID patients were unvaccinated (94.6%) and had, on average, one comorbidity. Hypertension (19.1%), immunocompromised condition (23.8%), mental health conditions (15%), obesity (10.8%), and cancer (11.2%) were the common prevalent comorbidities. The presence of comorbidity increased the risk of severe or critical COVID-19. COVID-19 cases were associated with the lack of vaccination and comorbidities. Effective vaccination strategies are needed to reduce the burden of COVID-19 in Colombia and, considering budgetary constraints, it is advisable to prioritize the elderly or populations with underlying conditions.